Scientific Writing Preparation Training for High School Teachers in Muara Gembong Regency - Daryati, Daryati; Arthur, Riyan; Maulana, Arris; Arifah, Shilmi; Maharani, Salma (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The low level of publication among high school teachers is an indication that the research conducted by teachers has not been fully disseminated. The purpose of this study is to provide technical guidance to teachers of SMA Negeri 1 Muara Gembong in improving the ability and quality of publication of their papers that can be used in the context of graduation or promotion/position as well as the component of assessing the portfolio of teacher certification in Indonesia. The methods used in this training include conducting discussions. The method is developed according to the situation and conditions that develop simultaneously and continuously. The population in this study is participants/teachers at SMA Negeri 1 Muara Gembong. The number of samples in this study was 25 participants or 25 teachers from various subjects at SMA Negeri 1 Muara Gembong. This training was conducted directly/offline in one of the SMA Negeri 1 Muara Gembong classes for approximately one day. The instrument used here is a questionnaire in the form of a survey of participant satisfaction with the presenters and the material that has been given. In addition, the results of this study received feedback. Namely, most participants stated that the speaker was very good at delivering material and asked for frequent training like this because the material was beneficial for the teachers there. This measure is intended so that the culture of teacher literacy and research will increase along with the rapid progress of educational science. That is, this community service activity is basically a form of concrete contribution of educational people in fulfilling the quality standards of higher education, especially in the standards of high school teacher graduates in Indonesia